The handbook of training technologies : (Pfeiffer, 2006)
This important resource offers an understanding of the basic principles that underlie training methods and the use of technology training in the workplace. The authors provide a primer for the four pervading and more advanced technologies used in business training¾the Internet, computer-based training, knowledge management systems, and decision support tools. Appropriate for those who have little or no formal training in educational technology, this book addresses such topics as the decision to use, the pros and cons for using, and presentation strategies for media as varied as the Internet, teleconferencing, videoconferencing, satellite distance learning, and electronic performance support systems.